Patient experience of care in a student-faculty collaborative practice - Rebecca Berman; Scott Elman; Pratyaksh Srivastava; Janine Knudsen; Laura Huppert; Kyle Dempsey; Michael Barnett; Camille Powe; Karen Donelan (The Beryl Institute, 2014)
Student Run Clinics (SRCs) are a popular means of caring for the underserved while providing valuable medical education opportunities. Reports of patient experience surveys are rare in this setting. This is troublesome because it is possible that underserved patients, who are more likely to receive care at SRCs, are not receiving the same level of care as at more traditional medical practices. The purpose of this research was to measure patient experience in a student-led medical clinic. The method included the use of patient experience surveys, which were self-administered pre-visit and self- and interviewer administered post-visit. The key results, 100% of patients felt treated with respect. 81.4% of patients would "definitely" and 16.3% would "somewhat" refer their family and friends to the clinic. 87% reported being seen within 15 minutes of their appointment time; 60% reported that they knew they would be seen by medical students and a doctor. This data has been useful to our student-led clinic in streamlining clinic flow, reducing wait times and building awareness of our structure. Our hope is this study will encourage others SRCs to adopt similar student-faculty collaborative research based practices to enhance care for SRC patients while teaching students to use patient feedback to improve quality of care.